A web-based student residential searching integrated with Google Maps and WhatsApp API: a case study of UiTM Arau Perlis / Nurul Izzah Mohd Azri ... [et al.] - Mohd Azri, Nurul Izzah; Osman, Mohd Nizam; Othman, Nor Arzami; Sedek, Khairul Anwar; Maghribi, Mushahadah (UiTM Cawangan Perlis, 2023)
Every year, the university receives many students from all over the state or country. Consequently, the college facilities at the university are unable to accommodate the volume of students who recently enrolled sufficiently. Besides, some old students do not get college facilities because the university gives those facilities to newly registered students. This causes some students to experience problems in finding a rental room that suits their needs. Therefore, a web-based Student Residential search integrated with Google Maps and WhatsApp API was designed and implemented, that allows students, especially non-resident students to find and rent rooms near UiTM Arau Perlis. The rental rooms displayed on this website are rental rooms that the landlord wants to rent. Landlords can register the rental rooms they want to rent by logging into the website, while tenants can only rent the house after logging in. Besides, the Student Residential Searching System also was integrated with the WhatsApp API, enabling the admin to notify the landlord if the information such as the electric or water bill they uploaded, was invalid for validation purposes. While the integration of Google Maps allowed students to search for rental properties based on location. The system uses the System Development Life Cycle (SDLC) by implementing the waterfall model as the methodology. Usability testing was conducted to determine user acceptance using a set of questionnaires, where thirty participants were chosen to test and evaluate the proposed system. The findings and analysis showed that the system was manageable, usable, and reached participants' expectations and achievement. Hence, the system helps the rental management between admin, landlord, and tenant to be more effective and smoother to complete the process.